Analisis Bentuk Penyajian Kesenian Dikir Kepri Bermadah Oleh Sanggar Saidina Ali, Pulau Lengkang - Feriyansyah Feriyansyah; Widyanarto Widyanarto (Dance and Theatre Review, 2022)
Analysis of the Art Presentation Dikir Kepri Bermadah by Saidina Ali Studio, Lengkang Island. Dikir Kepri art is an art that is formed from the reforms carried out on Western dikir art. This renewal was carried out by the Saidina Ali studio as the pioneer of the reform. The reforms carried out refer to the form of this art itself. This renewal was carried out to avoid cultural plagiarism because the basis for the birth of this art came from Malaysian art with the same form. the object under study. With stages consisting of literature study, interviews, and direct observation of the object being studied. The form of presentation of Dikir Bermadah can be analyzed from various aspects, namely: 1. analysis of dancers 2. analysis of songs and poetry 3. analysis of accompaniment music 4. symbolic analysis 5. analysis composition 6. analysis of fashion and property This research was conducted on Lengkang island with the Saidina Ali studio as the primary data source. With the guidance of Mr. Mizan, S.pd as a resource person, the learning process of the research object went smoothly. The form of presentation of the Dikir Kepri Bermadah and the difference with the Western Dikir can be seen clearly from various aspects in the form of presentation.Keywords: Thoughts of Mercy, Renewal, Form of Presentation